Compassionate use of new drugs in children and adolescents with multidrug-resistant and extensively drug-resistant tuberculosis: early experiences and challenges. Issue 3 (23rd June 2016) - Tadolini, Marina; Garcia-Prats, Anthony J.; D'Ambrosio, Lia; Hewison, Catherine; Centis, Rosella; Schaaf, H. Simon; Marais, Ben J.; Ferreira, Hannetjie; Caminero, Jose A.; Jonckheere, Sylvie; Sinha, Animesh; Herboczek, Krzysztof; et al.
The World Health Organization (WHO) estimated that 480 000 new multidrug-resistant (MDR) tuberculosis (TB) cases occurred globally in 2014, with 190 000 deaths. Limited data are available on the burden of MDR-TB in children. A recent systematic review estimated that 32 000 children acquire MDR-TB annually; of these, very few are correctly diagnosed and provided with appropriate treatment [1]. First experience and challenges of compassionate use of new anti-TB drugs to treat MDR- and XDR-TB in children http://ow.ly/SWXF300a0UX